Sensitivity of Harumanis Mango Seed (Mangifera indica L) Solution toward Aeromonas hydrophila - Telaumbanua, Siti; Lukistyowati, Iesje; Syawal, Henni (Jurnal Perikanan dan Kelautan, 2019)
Research was conducted from October to December 2017, at the labory Examination of Fish Disease, Fisheries and Marine Faculty of Universitas Riau. The Purpose of this study was to determine the sensitivity of harumanis mango seed (Mangifera indica L) as antimicrobial to A. hydrophila, the range of Minimal Inhibitory Concentration (MIC) and the lethal dose (LD50) harumanis manggo seed (M. indica L) solution against to catfish (Pangasius pangasius) (7-9 cm) by immersion. The research method used doses; D1: 100%; D2: 90%; D3: 80%; D4: 70%; D5: 60%; D6: 50%; D7: 40%; D8: 30%; D9: 20% D10: 10%, and K : Control (Oxytetracyclin).The results showed that mango seed solution was sensitive to A. hydrophila bacteri and was able to inhibit A. hydrophila up to 0.09% dose with inhibit zone of 7.31 mm. Minimum Inhibitory Concetrantion (MIC) is 0.1% (1000 ppm) number of colonies 270.66 CFU/ mL.The dose of LD50 is 2115,85 ppm